Optimization of Asymmetric Magnetic Recording Heads Inclination Angle and Study the Characteristics for a Higher Bit Density Recording of HDD - Idrees, Ammar I. (Science Journal of University of Zakho, 2018)
This paper study the optimization of the asymmetric magnetic recording heads, the calculations demonstrate sharp field gradient performance for both the horizontal, and vertical field components for this type magnetic recording heads at large inclination and small distance between the head and underlayer. In addition, the characteristics for a higher bit density recording of HDD have been studied. These characteristics can be utilized to raise bit density in both recording method conventional and vertical, respectively.
Keywords: Magnetic Recording; Asymmetrical Heads; Potential and head field